Spectroscopic, Structural and Solution Studies of New Tl(I) Complex with 3-Nitrobenzylidene-4-aminobenzoic Acid - Rahimi*, Rahmatollah; Esk, Maryam (Asian Journal of Chemistry, 2011)
A new thallium(I) complex with a Schiff base ligand, [Tl(L)](1) [L– = 3-nitrobenzylidene-4-aminobenzoic acid], has been synthesized and characterized. The carboxylic groups of the ligand 3-nitrobenzylidene-4-aminobenzoic acid in the new Tl(I) complex is chelated via oxygen atom of acidic group. The formation and stoichiometry of the Tl+-L complex in DMF solution was investigated by spectrophotometric and conductometric method. The UV spectra of Tl(I) compelex shows that the thallium-oxygen bonds have considerable covalent character.